A novel bio-inspired approach for VM load balancing and efficient resource management in cloud. (14th June 2022) - Assudani, Purshottam J.; Balakrishnan, P.
In cloud, balancing the load on virtual machines (VMs) and efficient utilisation of resources is very crucial and challenging, which becomes complex due to heterogeneous nature of VMs and user's tasks in distributed environment. To maintain the service quality, it is mandatory that users' tasks should be scheduled efficiently with immediate response, while satisfying QoS needs mentioned in service level agreement (SLA). Concerning these issues, researchers have designed bio-inspired algorithms to solve optimisation problems for resource scheduling. In this paper, we have proposed a bio-inspired method namely inventive particle swarm optimisation (IPSO), which not only schedules user's task efficiently, but also uniformly distributes the load among different VMs. Additionally, we have also designed another algorithm named as merge sort with divide and conquer (MSDC) approach to allocate the resources in cloud dynamically in an efficient manner. The experimentation is done on CloudSim simulator, which shows that proposed algorithms give better response time, VM utilisation and execution time.